Early Puberty in Children: Psychological, Social, and Parental Impacts - Azizah Yuhani; Dhesi Ari Astuti; Cesa Septiana Pratiwi (Journal of Community Health Provision, 2026)
Precocious puberty, or sexual development that occurs earlier than normal, has significant implications for child development. This scoping review aims to map the existing literature on the psychological and social impacts of precocious puberty in children, and the role of parents in dealing with it. a systematic literature search was conducted in PubMed, ScienceDirect, Scopus databases, using Research-Rabbit and Google Scholar search engines. Inclusion criteria included studies that examined the psychological and/or social impacts of precocious puberty in pre-adolescent and early adolescent children, and discussed the role of parents in this context. Data were extracted regarding study characteristics, definition and measurement of precocious puberty, reported psychological and social impacts, and how the role of parents was conceptualized. Narrative synthesis was used to summarize the findings. The review identified five relevant articles. Findings suggest that earlier pubertal timing is associated with increased risk of mental health problems and decreased emotional quality of life. Social challenges such as bullying were also reported. The role of parents appears to be crucial, with social support correlated with children’s readiness for change, and parenting style mediating the effect of parental stress on children’s behavioral problems. Broader social determinants, such as peer support and school environment, also play a role in the psychological well-being of adolescents with early puberty. Early puberty is a complex phenomenon with significant psychological and social consequences for children. Social support from the environment, especially parents, plays an important role in mitigating negative impacts. Further research, especially longitudinal studies and those that consider the socio-cultural context, is needed for a deeper understanding and development of effective interventions.